2001
DOI: 10.1006/viro.2000.0713
|View full text |Cite
|
Sign up to set email alerts
|

Cell Fusion Induced by Herpes Simplex Virus Glycoproteins gB, gD, and gH-gL Requires a gD Receptor but Not Necessarily Heparan Sulfate

Abstract: To characterize cellular factors required for herpes simplex virus type 1 (HSV-1)-induced cell fusion, we used an efficient and quantitative assay relying on expression of HSV-1 glycoproteins in transfected cells. We showed the following: (1) Cell fusion depended not only on expression of four viral glycoproteins (gB, gD, and gH-gL), as previously shown, but also on expression of cell surface entry receptors specific for gD. (2) Cell fusion required expression of all four glycoproteins in the same cell. (3) He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
348
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(361 citation statements)
references
References 67 publications
8
348
1
1
Order By: Relevance
“…HSV-1 gH is present on the surface of infected cells and virus particles as a heterodimer with gL (6), and gL is absolutely required for cell-cell and virus-cell fusion (24,47). It is not clear at present whether gL has a role in hemifusion other than to ensure the appropriate folding and localization of gH.…”
Section: Discussionmentioning
confidence: 99%
“…HSV-1 gH is present on the surface of infected cells and virus particles as a heterodimer with gL (6), and gL is absolutely required for cell-cell and virus-cell fusion (24,47). It is not clear at present whether gL has a role in hemifusion other than to ensure the appropriate folding and localization of gH.…”
Section: Discussionmentioning
confidence: 99%
“…Fusion of cells mimics the fusion of virion and target cells that occurs during viral entry (36). In this experiment, Chinese hamster ovary (CHO-K1) cells, designated "effector" cells, were generated.…”
Section: -O-sulfated Octasaccharide Inhibited Herpes Simplex Virus 1mentioning
confidence: 99%
“…More recent studies of recombinant viruses with specific deletions in gB has shown that gB is essential for the production of infectious virus (21,22). Finally, gB coexpressed with other viral glycoproteins is required for cell-cell fusion in cell-based fusion assays for pseudorabies virus, HSV-1, HSV-2, and EBV (8,[23][24][25][26][27].gB is one of the most conserved proteins within the herpesvirus family and consists of a large amino-terminal ectodomain, This paper was submitted directly (Track II) to the PNAS office.Abbreviations: HHV, human herpesvirus; HSV, herpes simplex virus; ER, endoplasmic reticulum; EBV, Epstein-Barr virus; HEK, human embryonic kidney; CHO, Chinese hamster ovary. …”
mentioning
confidence: 99%
“…More recent studies of recombinant viruses with specific deletions in gB has shown that gB is essential for the production of infectious virus (21,22). Finally, gB coexpressed with other viral glycoproteins is required for cell-cell fusion in cell-based fusion assays for pseudorabies virus, HSV-1, HSV-2, and EBV (8,[23][24][25][26][27].…”
mentioning
confidence: 99%
See 1 more Smart Citation